Translator's Forward and Commentary: "Appreciation" by Jean Ricardou - Michel Sirvent (Studies in 20th & 21st Century Literature, 1991)
Translator's Forward and Commentary: "Appreciation" by Jean Ricardou
Keywords: Jean Ricardou; Appreciation; translator; translation